2022
DOI: 10.1016/j.ijid.2021.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive deficits and sequelae following severe hand, foot, and mouth disease from 2009 to 2017, in JiangSu Province, China: a long-term follow-up study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In this study, we found that children who lived in the rural areas were more likely to develop severe HFMD, which is in line with previous studies in Guangxi [20]. Previous studies have found that poor medical conditions and poor guardian awareness of HFMD treatment are the influencing factors for the development of severe HFMD and mortality in rural areas in China [21][22][23]. Meanwhile, rural patients are more willing to seek medical treatment nearby, which is a possible reason for the higher mortality of HFMD in rural areas.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that children who lived in the rural areas were more likely to develop severe HFMD, which is in line with previous studies in Guangxi [20]. Previous studies have found that poor medical conditions and poor guardian awareness of HFMD treatment are the influencing factors for the development of severe HFMD and mortality in rural areas in China [21][22][23]. Meanwhile, rural patients are more willing to seek medical treatment nearby, which is a possible reason for the higher mortality of HFMD in rural areas.…”
Section: Discussionsupporting
confidence: 91%
“…At a mean age (SD) of 55.6 (6.9) months old, children’s cognitive development was assessed by using the Chinese version of Wechsler Preschool and Primary Scale of Intelligence-Fourth Edition (WPPSI-Ⅳ CN), which has high reliability and validity [ 21 , 22 ] and can be used in children aged 2.5–6 years. In detail, children aged 30–47 months ( n = 202) were required to complete 7 subtests to synthesize 4 indexes as verbal comprehension index (VCI, including information, receptive vocabulary and picture naming), visual space index (VSI, including block design and object assembly), working memory index (WMI, including picture memory and zoo locations) and full-scale intelligence quotient (FSIQ, calculated based on the above 3 indexes).…”
Section: Methodsmentioning
confidence: 99%
“…Throughout earlier outbreaks of HFMD around the world, different clinical features have been observed in accordance with the virulence of the virus responsible for the outbreak [ 22 ]. The primary symptoms observed in the recent outbreak of ‘Tomato flu’ in India – namely, fever, anorexia (loss of appetite), nausea, vomiting, diarrhea, dehydration, swollen joints and body pain – are similar to that of other viral infections.…”
Section: Methodsmentioning
confidence: 99%